Strategi Pemeliharaan Aset Publik Dalam Mendukung Keberlanjutan Operasional Pemerintah Daerah - Melani Malindo; Eli Apud Saepudin; Syendy Ardiansyah; Nanda Putra Pajar; Rika Aprilliyanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Public assets play a strategic role in supporting governmental operations and public service delivery at the local government level. The condition and performance of public assets are crucial in ensuring operational sustainability. However, in practice, public asset maintenance is often reactive and insufficiently integrated into long-term development planning. This study aims to analyze public asset maintenance strategies and their role in supporting the operational sustainability of local governments. A qualitative approach with a descriptive-analytical design was employed. Data were collected through in-depth interviews, field observations, and documentation studies involving local government agencies responsible for asset management. Data analysis was conducted using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that public asset maintenance strategies are predominantly corrective, while preventive and condition-based maintenance have not been optimally implemented. Key constraints include limited policy support, weak institutional coordination, budget constraints, insufficient human resource capacity, and underutilization of asset information systems. The study concludes that well-planned, preventive, and integrated asset maintenance strategies are essential to maintaining asset performance and ensuring the operational sustainability of local governments.